A comparison of efficacy of diclofenac patch and physical therapy techniques in the treatment of patients with myofascial pain disorder of the upper trapezius - Komal Razzaq; Umair Arif; Rabia Javaid; Hafiz Muhammad Almas Sabir; Attia Noreen; Maryam Ashfaq; Ramish Akram (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2021)
Objective: This study was conducted to find the best treatment in treating the patients of myofascial syndrome for this purpose two treatment options were compared to rule out the best option of treatment in minimizing the pain, enhancing the cervical movement and in determining the pressure pain threshold of MTrp. Material and methodology: It was a comparative study. Total 60 patients were randomly allocated to each group of treatment. We compared two treatments, treatment A of 30 patients was physical therapy and 30 patients of treatment B was diclofenac patch. For seven days, these patches were applied three times per day to the MTrP area of the upper trapezius muscle. The fix's sufficiency and security boundaries were evaluated before it was used (day 0), three days later (day 3), and six days later (day 6). Chi square test was used for checking association of treatments and different attributes of patients.  Results: There is significance association was found between demographic characteristics and treatments groups with p-values less than 0.05. There is significance difference effect between both treatments using VAS pain scale and cervical active Rom and PPT of MTRP using p-value less 0.05. These results shows that physical therapy treatment effects are batter as compare to diclofenac patch. Conclusion: Physical therapy techniques and the diclofenac patch have both been shown to be helpful but significant results are shown by Group A in treating trigger points of upper trapezius by normalizing the pathophysiological reasons of trigger points of this region. Physical therapy techniques are more helpful in reducing pain and in achieving cervical movement.